2008
DOI: 10.1111/j.1572-0241.2007.01546.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gastroesophageal Reflux on Survival in the Community

Abstract: In this population-based study with over 50,000 person-years of follow-up, reflux symptoms were not associated with worse survival. The vast majority of heartburn sufferers can be reassured of the benign nature of their condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
3
10
1
Order By: Relevance
“…The results of this study align with those from a smaller population-based cohort study from the USA, which found no difference in all-cause mortality between 115 individuals with daily and 2708 individuals without reflux symptoms 18. A cohort study from the UK found that patients with GORD (n=7159) had a 60% increased all-cause mortality within the first year of follow-up after inclusion, compared with patients without GORD (n=10 000), but no difference was seen for the remaining 4 years of follow-up 19.…”
Section: Discussionsupporting
confidence: 87%
“…The results of this study align with those from a smaller population-based cohort study from the USA, which found no difference in all-cause mortality between 115 individuals with daily and 2708 individuals without reflux symptoms 18. A cohort study from the UK found that patients with GORD (n=7159) had a 60% increased all-cause mortality within the first year of follow-up after inclusion, compared with patients without GORD (n=10 000), but no difference was seen for the remaining 4 years of follow-up 19.…”
Section: Discussionsupporting
confidence: 87%
“…16 As circulatory diseases are the major causes of death in the United States, 28 it is likely that this inverse association was mainly related to circulatory diseases, consistent with our finding. The reason for this inverse association is unclear.…”
Section: Discussionsupporting
confidence: 86%
“…15 Finally, a study from the United States showed no association between daily GERD symptoms and mortality, and there were inverse associations between weekly and less than weekly symptoms and mortality. 16 There has been no published population-based study from non-Western countries on the association between GERD and overall mortality. …”
Section: Introductionmentioning
confidence: 99%
“…Individuals with long‐standing GERD have an increased risk of oesophageal adenocarcinoma 38 . Mortality in individuals with GERD has been reported to be increasing, 39 although a recent study showed that reflux symptoms were not associated with worse survival 40 . There is no confirmation that PPIs prevent BO or adenocarcinoma, but some uncontrolled studies suggest that they may reduce the progression of Barrett’s epithelium to dysplasia 41, 42 .…”
Section: Discussionmentioning
confidence: 99%